DPRK and the CTBT: What Could Come Next after the Moratorium? - Qiyang Niu; Haeyoon Kim; Zhaniya Mukatay (Journal for Peace and Nuclear Disarmament, 2022)
At the 25th anniversary of the opening for signature of the Comprehensive Nuclear-Test-Ban Treaty (CTBT), this paper seizes the opportunity of a self-imposed nuclear test moratorium by the Democratic People’s Republic of Korea (DPRK), analyzes Kazakhstan’s experience in dismantling its nuclear test site, and proposes three policy recommendations as potential solutions to stir the DPRK to join the CTBT: First, the international community should count DPRK’s potential signing of the CTBT as a reason to consider relaxing sanctions against DPRK in the future; second, the international community should encourage the DPRK to vote in favor of UNGA resolutions on the CTBT as a first step forward towards the final signing; third, the international community and the CTBTO Preparatory Commission (CTBTO) should consider inviting the DPRK for CTBTO training and workshops to build trust. Together, these actions could not only push forward the CTBT with its coming into force but also melt the current stalemate of engaging with the DPRK positively.